Displaced margins and misplaced equity: Challenges for South African higher education - Pillay, V. (South African Journal of Higher Education, 2019)
This paper makes a single point: that the goal of institutional diversity falls short of the goal of equity in higher education. Put differently, while the margins for diversity have increasingly been displaced and dislocated, equity appears to be misplaced. I contend that through significantly increased access, the South African education system has made remarkable progress in achieving racial, ethnic and gender diversity in their student populations. Despite these achievements in diversity, however, equity, measured through the graduation rates of historically disadvantaged students, trails behind diversity achievements. At the risk of taking a parochial posture, my goal is use the challenges of the mature (American) and relatively immature higher systems (South African) to point to ‘lessons’ that may be locally valuable. I draw on selected quantitative data that illustrates the trends in diversity and equity. I use the challenges with respect to diversity and equity in the United States system as a foil against which to read the South African quantitative trends. In so doing I show that time and maturity, demonstrated through the highly reputed American system, may not fix issues of equity and that conscious and that the South African system requires active interventions to address these challenges.